TEACHING METHODOLOGY OF CARVING TECHNIKQUE IN ALPINE SKING - Rašid Hadžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The most modern skiing technique used today is carving. In this technique the most important is load on the skies-centre of gravity disposition. The other important thing is that skier has to put a little wider apart his legs, at hips expanse mostly. Such position insures bigger firmness. We can see when carving curve performance is successful by skiing mark on the snow. There should be only two lines because there is no losing of direction. Driving this way, skier drives most of the time on the ski edges. Playgrounds are very important in process of learning carving technique because they enable speed control and choice of ideal skiing line. Placed playgrounds, appropriate for terrain, enable give us a total control of tasks which students have to perform. When making playgrounds we have to obey basic rules of gradual weight increasing and returning to simple (easier) positions, at the same time.